Elemental, Isotopic, and Pesticide Analysis of Wild and Cultivated Berries. (22nd November 2017) - Covaciu, F. D.; Magdas, D. A.; Dehelean, A.; Feher, I. C.; Radu, S.
ABSTRACT: The focus of this study was to investigate differences in isotopic, elemental, and trace pesticide concentrations of wild and cultivated berries from Transylvania. To emphasize differences based on geographical origin, stable isotopic ratios of 2 H/ 1 H, 18 O/ 16 O, and 13 C/ 12 C were determined by isotopic ratio mass spectrometry. Elemental fingerprinting of berries was performed by inductively coupled plasma mass spectrometry. The determination of trace pesticides in berries was performed by gas chromatography–mass spectrometry. Differences between wild and cultivated berries were evaluated using multivariate statistical analysis. The results suggest that multielemental, isotopic, and trace pesticide fingerprinting is feasible for sample differentiation.